Real-world treatment patterns, comorbidities, and disease-related complications in patients with multiple myeloma in the United States. (2nd January 2016) - Song, Xue; Cong, Ze; Wilson, Kathleen
Abstract: Objectives: To describe multiple myeloma (MM) treatment patterns and comorbidities over time in the US. Research design and methods: Study patients were newly diagnosed with MM (ICD-9-CM 203.0x) between 1 July 2006 and 31 March 2014 and had ≥6 months of data prior to the initial MM diagnosis in MarketScan Research Databases. Patients were followed until inpatient death or the end of data. First-line, second-line, and third-line treatment regimens were identified following diagnosis and were described over time based upon the start date of the first line of therapy (2006–2007, 2008–2014, 2013–2014). Comorbid conditions and disease-related complications were examined during the 6 months prior to the line of therapy start dates. Results: A total of 24, 507 MM patients were examined (mean age: 65.2 years, 54.1% male, mean follow-up: 23 months, 16.2% transplant). Across all lines of therapy, the proportion of patients on thalidomide-based regimens decreased over time. In the first line, bortezomib-based regimens became more common from 2006–2007 to 2008–2014 (2006–2007: 17.0%, 2008–2014: 44.3%, 2013–2014: 49.4%). In the second line, lenalidomide- and bortezomib-based regimens were the most common (2013–2014: lenalidomide: 28.9%, bortezomib: 26.2%). The combination regimen of lenalidomide + bortezomib became more common in the first and second lines. In the third line, carfilzomib- and/or pomalidomide-based regimens were 37.0% in 2013–2014. Skeletal-related events, hypertension, anemia, and chronic kidney disease were the most prevalent comorbidities and disease-related complications. During the 6 months prior to each line of therapy, the prevalence of the majority of the comorbidities and complications increased as patients progressed to higher lines of therapy. Conclusions: MM treatment patterns have been dynamic over time. Comorbid conditions and myeloma-related complications increase as patients progress and may worsen MM patients' prognoses over time. Combination regimens such as lenalidomide + bortezomib are more widely used as first- and second-line therapy. Newly approved agents (carfilzomib, pomalidomide) are the prevailing treatments in the third line and are under further investigation for earlier lines of therapy.